(3HZjI GdWdH aj JGQjN MdHs - (3YeQ Hf CMeO Hf gHI Gddg Hf CHj LQGOI GdYbjdj, ceGd GdOjf GHf GdYOje,J (B660 (3g` s
(3ChdgG (B:s
(3jHJOF HJQLeI QGLM Hf GHQGgje GdejhQbi s
(3BNQgG (B:s
(3jfJgi HJQLeI Rfci Hf Bb SfbQ CHh GdeXaQ GdJQci s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B275s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B332 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B48 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs